Power quality improvement by pre-computed modulated field current for synchronous generators - Fallows, Daniel; Nuzzo, Stefano; Costabeber, Alessandro; Galea, Michael (2017)
Although power quality aspects of electrical machines have been extensively studied and investigated for a large number of years, room for improvement still exists in the field of classic, wound-field, synchronous generators. This paper proposes an innovative method of power quality improvement for single-phase synchronous generators in which the usual DC field current is replaced by a calculated current waveform. The optimised field current waveform is designed in such a way that harmonics created by the machine geometry and the winding configuration are significantly reduced.